Analisis Kinerja R290 sebagai Pengganti R32 pada Unit AC-Split Kapasitas 9,000 Btuh/hr - Widodo; Ade Irvan Tauvana; Fatkur Rachmanu; Lukman Nulhakim; Syafrizal; Mokhamad Is Subekti (Fakultas Teknik Universitas Pancasila, 2022)
R290 is a type of natural refrigerant that has ODP = 0 and GWP = 4. While R32 from synthetic materials has ODP= 0 and GWP = 675 both are refrigerants used in Split AC. With this high GWP, it can have a damaging impact on the atmosphere. The advantage of R290 is that it has a lower density compared to R32, which can save the number of fillings in the AC unit by ±30% of the previous amount of refrigerant in the same volume. R290/R32 was flammable with LFL= 2%/13% and UFL= 10%/33%. The purpose of this study was to analyze the performance of R290 as a substitute for R32 on an AC-split unit with a capacity of 9,000 Btuh/hr. The steps used in the test are that the AC unit is placed in an open room with ambient temperature around 32°/80°C. The test was carried out until it reaches the optimal and stable temperature, then data is collected. The results of data collection from the evaporator air temperature R290/R32 = 21.4°C/23.0°C, condenser air temperature = R290/R32= 35°C/38.5°C, suction pressure= 90 psig/130 psig and discharge 200 psig/420 psig. The test data were analyzed and calculated using the Mollier Chart software with the results = R290/R32 = refrigeration effect = 344.8/272.2 kJ/kg, compression work = 12.18/13.02 kJ/kg, COP = 28.3/20.9, compression ratio = 2.2/3.2, strong electric current 4.98/5.73 A. From the decrease in electric current of R290 obtained a savings of 13.3% was obtained when converted to electricity bill payment and get a profit of 45,886/month.